Challenges in Technology Integration for Online Teaching and Learning for English Sessional Academics - Priscilla Shak; Wendy Hiew; Bernadette Tobi (CALL-EJ, 2022)
The new norm, post-COVID-19, is characterized by the worldwide espousal of the virtual classroom. While full-time university academics are typically provided with continuous training support for their technology integration in online teaching, this is not so for sessional academics, who are inadvertently deprived of such opportunities. This would subsequently threaten the quality of online lessons, which could potentially affect students’ learning. The main aim of this study was to identify the problems sessional academics faced when conducting online lessons. In addition, it also sought to identify their training needs so that the necessary training support could be provided to them. Twenty-one sessional academics from the English language unit of a public university in Malaysia participated in this study while under the movement control order period. Qualitative data was collected through individual interviews designed to obtain feedback regarding their online teaching experience, problems with online teaching, and training needs. Findings revealed that despite their readiness for online teaching and learning, there were context-specific issues related to the lack of training that affected this group of academics’ efficacies in conducting online language lessons.